The Unsaid in Chomsky’s Theory of Language and Pragmatics - KAOUACHE, Salah (Journal of Human Sciences, 2015)
There is a common belief among EFL learners and their teachers alike that the unsaid information is a specificity of pragmatics and pragmatics only. In the domain of linguistics it is made clear that semantics and pragmatics are the two disciplines which look at the knowledge used to convey and to extract meaning when speaking or hearing someone speak. It is also clear-cut that, generally speaking, semantics is concerned with meaning that comes from linguistic knowledge, while pragmatics is concerned with meaning that takes into consideration knowledge about the social world. That is, the pragmatic meaning cannot be predicted by linguistic knowledge alone.The aim of this paper, however, is to show that the standpoint that the unsaid information is a property of pragmatics only is debatable. The unsaid information, yet understood, is introduced in Chomsky’s theory of language, namely in his transformational grammar. The only thing is, in pragmatics, the unsaid is understood by implication, whereas in Chomsky’s grammar, the unsaid is understood by intuitions which are part of the speaker’s language.